John IV with Blake and Crystal Eastin
Blake Eastin (Crystal's father), Crystal Eastin, John Steinbeck IV. John IV and Crystal had a daughter, Blake, named after Crystal's father. There are seven other photographs of Crystal with John IV, her mother, and her daughter, Blake. All can be found under this photo number.